Editorial: Gen Z Movement in Nepal: Reshaping the New Political Landscape - Chaudhary, Deepak (Journey for Sustainable Development and Peace Journal, 2026)
The Gen Z movement, characterized as a digital-first mobilization in Nepal, prioritizes issue-based activism over traditional party politics. It focuses heavily on governance matters such as corruption, unemployment, inequality, and a lack of accountability. Gen Z is reshaping the political environment in Nepal and is anticipated to play a crucial role in future governance, youth engagement, and the emergence of individual professional leaders.